Analisis perbedaan indeks glikemik dan beban glikemik pada berbagai jenis minuman kekinian: Peningkatan risiko metabolik - Aisyah Luthfia Agung; Elvi Susanti; Diah Retno Wahyuningrum; Joko Cahyono (Poltekkes Kemenkes Aceh, 2025)
Background: Indonesia ranks third highest in consumption of contemporary drinks in Southeast Asia. It contains high sugar levels and if consumed excessively can significantly increase blood glucose. Glycemic Index (GI) and Glycemic Load (GL) are ways to determine the rising of blood sugar levels.Objectives: To determine the differences in glycemic index and glycemic load of various contemporary drinks.Methods: The type and design of the study used was quasi-experimental with non-equivalent control group design. Quasi-experimental is an experimental study consisting of a treatment group and a control group. Respondents were divided into 4 groups (control, boba, thai tea, and coffee latte) and consisted of 8 people in each group. Blood glucose examination was carried out through the capillary at minutes 0, 30, 60, 90, and 120 to assess the blood glucose response. Data were analyzed using the One Way Anova test and the Post Hoc Tukey follow-up test.Results: GI boba, thai tea, and coffee latte were respectively (62,20%; 69,,13%; 99,97%) and GL respectively (27,36%; 30,62%; 44,77%). Boba and Thai tea are classified as medium IG with high BG, while coffee latte is classified as high IG with high BG. A significant difference was shown between the IG of coffee latte and the control (0,008) and the BG of the three contemporary drinks with the control (0,000). Conclusion: There is no difference in meaning between GI and GL of the three types of contemporary drinks. It is recommended that contemporary drinks are not consumed every day.